Features of Customs Audit and Its Conduct - Saifullayevich, Saifullayev Mehrozh (Universitas Muhammadiyah Sidoarjo, 2020)
This article contains the essence of the concept of customs audit, definitions of the concept of customs audit by foreign and domestic scholars, the procedure for conducting a customs audit, the scientific basis of customs audit, which differs from customs control.